2022
DOI: 10.1007/s00404-022-06805-9
|View full text |Cite
|
Sign up to set email alerts
|

Integrative analysis of the immune-related ceRNA network in fetal growth restriction based on weighted gene co-expression network analysis

Abstract: Immune disorders lead to placental dysfunction and fetal growth restriction (FGR), but current research on the immune regulation mechanisms of FGR is insufficient. Therefore, this study aimed to construct an immune-related competing endogenous RNA (ceRNA) network to predict FGR onset risk. Methods: Based on microarray data from the GEO database, CIBERSORT was used to analyze immune cell infiltration. Weighted gene co-expression network analysis (WGCNA) was used to screen immune-related module genes with differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Recent research has revealed that dysregulated lncRNAs can be used as predictors and can play a significant role in maternal and baby disorders caused by hypoxia. The coexpression of lncRNAs and circRNAs as well as the ceRNA network are not fully understood, although there have been numerous pertinent studies [ 29 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent research has revealed that dysregulated lncRNAs can be used as predictors and can play a significant role in maternal and baby disorders caused by hypoxia. The coexpression of lncRNAs and circRNAs as well as the ceRNA network are not fully understood, although there have been numerous pertinent studies [ 29 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…The decreased mRNA levels of MEK1 and MAPK can induce FGR, suggesting that MEK1 and MAPK mRNA play a role in the pathogenesis of FGR. Abnormal expression levels of MEK1 and MAPK mRNA may also be one of the reasons for the induction of FGR [21][22][23][24].…”
Section: Discussionmentioning
confidence: 99%